Third-generation solid dispersion combining Soluplus and poloxamer 407 enhances the oral bioavailability of resveratrol - Vasconcelos, Teofilo; Prezotti, Fabiola [UNESP]; Araujo, Francisca; Lopes, Carlos; Loureiro, Ana; Marques, Sara; Sarmento, Bruno (Elsevier B.V., 2021)
Resveratrol is a very promising anti-oxidant drug candidate with low oral bioavailability due to its intrinsic poor water solubility, intestinal efflux and metabolization mechanisms. Resveratrol solubility high-throughput screening with different carriers was performed showing an enhancement above 2000-fold with Soluplus (R) and Tween (R) 80. The former was selected as a carrier at the ratio of resveratrol: Soluplus (R) (1:2). Then, third-generation solid dispersions were developed with Gelucire (R) and poloxamer 407 at 5 and 15% to resveratrol: Soluplus (R) (1:2). All formulations enhanced solubility around 2-fold when compared to resveratrol: Soluplus (R) (1:2) solid dispersion. Caco-2 cells permeability studies showed that both surfactants increased drug permeability and the fraction recovered (2-fold) suggesting that these could reduce efflux mechanism and metabolism. Formulation with 15% poloxamer 407 demonstrated most promising results and was selected for further studies. In in vivo studies, resveratrol:Soluplus (R): poloxamer 407 (1:2-15%) third generation solid dispersion presented an AUCo-t of 279 +/- 54 ng.h/mL and a Cmax of 134 +/- 78 ng/mL, 2.5 fold higher than solid dispersion without poloxamer 407. This work reports the development of third-generation solid dispersion that significantly improved resveratrol bioavailability. This was accomplished by an increased solubility and most probably by reducing intestinal efflux and metabolism mechanisms.
Keywords: Solid dispersions; Bioavailability; Amorphous; Permeability enhancer; Metabolism inhibitor; Resveratrol